Three-Point Vertical Mattress Suture: A Simple Technique for Mild Blepharoptosis Correction in Partial-Incision Double-Eyelid Surgery - Chen, Bo; Ma, Li; Wang, Jingyi (Facial Plastic Surgery, 2023)
The aim of this study was to introduce a simple technique for mild blepharoptosis correction using a three-point vertical mattress suture in partial-incision double-eyelid surgery. The medical records and preoperative and postoperative images of 57 patients who underwent simultaneous mild blepharoptosis correction and partial-incision double-eyelid surgery from January 2018 to July 2021 were retrospectively reviewed. The surgical procedure mainly involves three small incisions in the proper eyelid crease, levator aponeurosis exposure by conservative dissection, and three-point vertical mattress suture to plicate levator aponeurosis and fix the orbicularis muscle with the plicated levator aponeurosis. All patients underwent bilateral partial-incision double-eyelid surgery: 10 unilateral and 47 bilateral blepharoptosis corrective surgeries. The average age was 25.3 ± 7.4 years. The mean operative and follow-up duration were 50 minutes and 13 months, respectively. The pre- and postoperative mean marginal reflex distance was 3.04 ± 0.27 and 3.75 ± 0.35 mm, respectively. The overall surgical success rate was 93%. Complications including undercorrection (5.3%), asymmetry (7.0%), and double-eyelid crease disappearance (5.3%) were reported. Three-point vertical mattress suture is considered an effective, safe, and simple technique for mild blepharoptosis correction in partial-incision double-eyelid surgery.
Keywords: blepharoptosis; double-eyelid surgery; partial incision; vertical mattress suture; marginal reflex distance